MANAJAMEN TANAMAN DI NURSERI KRANGGAN, BEKASI, JAWA BARAT - Hotmaulina Sihotang; Marina Silalahi; Erni Murniati Simalango (Jurnal Pro-Life, 2019)
Nurseri is a location for seedling, maintenance, selling and purchasing of various types of plants found in big cities including Jabodetabek. This study aims to reveal nurseri management in the Kranggan area to support the sustainability and development of the nurseri. This research was conducted by intensively interviewing all owners (6 persons). Kranggan Nurseri has an area of ​​100-500 m2 with the number of managers between 2-8 persons, depending on the area and the volume of plants being traded. Nurseri owners and managers apply various managements in the seedlings, maintenance, placement, and selection of plant species by considering the volume and the processing time. Many consumers purchase due to the small size, easy maintenance and seedling. Management knowledge is gained from the experience during trading or information exchange with other nurseri traders or managers. Plant placement in the nurseri is adjusted to the needs of light, habitus, aesthetics, and plant canopies. Korean banyan (Ficus compacta) is very potential to be developed in the yard because it has attractive leaf, branching, fruit and canopy characteristics but it does not require extensive land so it is believed to have good prospect to be traded with high economic value in nurseries. Keywords: Ficus compacta, nurseries, management, Bekasi